Two body final states production in electron-positron annihilation and their contributions to (g − 2) μ - Shi-Jia Wang; Zhen Fang; Ling-Yun Dai (Journal of High Energy Physics, 2023)
Abstract In this paper, we study the processes of e + e − annihilation into two body final states, either two pseudoscalar mesons or one meson with a photon. The hadronic vacuum polarization form factors are calculated within the framework of resonance chiral theory in the energy region of E ≲ 2 GeV, with final state interactions taken into account. A joint analysis on the processes of e + e − → π + π − , K + K − , K L 0 K S 0 $$ K_L^0K_S^0 $$ , π 0 γ, and ηγ has been performed, and the latest experimental data are included. Based on the vacuum polarization form factors of these processes, we estimate their contributions to the lowest order of anomalous magnetic moment of the muon, (g – 2) μ . Combined with other contributions from hadronic vacuum polarization and other interactions from the standard model, the discrepancy between theoretical prediction and experimental measurement is ∆a μ = (24.1 ± 5.4) × 10 −10, i.e., 4.5σ.